2013
DOI: 10.1063/1.4825130
|View full text |Cite
|
Sign up to set email alerts
|

High quality relaxed germanium layers grown on (110) and (111) silicon substrates with reduced stacking fault formation

Abstract: Epitaxial growth of Ge on Si has been investigated in order to produce high quality Ge layers on (110)- and (111)-orientated Si substrates, which are of considerable interest for their predicted superior electronic properties compared to (100) orientation. Using the low temperature/high temperature growth technique in reduced pressure chemical vapour deposition, high quality (111) Ge layers have been demonstrated almost entirely suppressing the formation of stacking faults (< 107 cm−2) with a very low r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 33 publications
(51 reference statements)
4
19
0
Order By: Relevance
“…The measured intensity distributions were well described by Gaussians, which enabled us to use a small number of parameters associated with the shape and treat them in a manner similar to the modified Williamson-Hall plot. The misfit dislocations were found to be strongly positionally correlated, and the density of threading dislocations for the Ge/Si(111) layers were in qualitative agreement with TEM observations (Huy Nguyen et al, 2013). corresponds to the interface where misfit dislocations are lying.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The measured intensity distributions were well described by Gaussians, which enabled us to use a small number of parameters associated with the shape and treat them in a manner similar to the modified Williamson-Hall plot. The misfit dislocations were found to be strongly positionally correlated, and the density of threading dislocations for the Ge/Si(111) layers were in qualitative agreement with TEM observations (Huy Nguyen et al, 2013). corresponds to the interface where misfit dislocations are lying.…”
Section: Discussionsupporting
confidence: 80%
“…The density of the threading dislocations is underestimated. One of the reasons may be that we did not include the broadening due to the stacking faults (Huy Nguyen et al, 2013). The incorporation of stacking faults into the current formalism will be the topic of future investigations.…”
Section: Figurementioning
confidence: 99%
“…However, the 4.2% lattice mismatch between Si and Ge precludes the direct epitaxial growth of high-quality relaxed Ge layers on top of Si wafers. Efforts to overcome this difficulty are still ongoing in Ge-related research [45][46][47][48]. In our study, high-quality Ge channels were successfully grown on top of Si (001) substrates using a two-temperature method.…”
mentioning
confidence: 99%
“…The Ge epilayers were grown on standard p − -Sið001Þ substrates using the twotemperature growth method by reduced pressure-chemical vapor deposition [46,48]. The structure consisted of a 1-μm-thick undoped Ge epilayer and a 50 nm heavily n-type doped Ge epilayer with a phosphorous doping concentration of ∼1.0 × 10 19 cm −3 and a degree of relaxation of 104%, calculated from the analysis of measured high-resolution x-ray diffraction symmetrical and asymmetrical reciprocal space maps.…”
mentioning
confidence: 99%
“…Indeed, it has been observed that the appearance of twins during epitaxial growth of Si wafers resulted in faulty devices, while for other defects, such as e.g. extrinsic stacking faults, it did not 44 45 46 (albeit perfect Ge crystals have been grown in the [111] direction as well 33 ). This may be of importance in GST materials where high contrast between amorphous and crystalline phases in terms of these properties is desired.…”
Section: Discussionmentioning
confidence: 99%